2022
DOI: 10.1007/s40747-022-00669-x
|View full text |Cite
|
Sign up to set email alerts
|

Hesitant T-spherical Dombi fuzzy aggregation operators and their applications in multiple criteria group decision-making

Abstract: A hesitant fuzzy (HF) set is an extension of the fuzzy sets and a T-spherical fuzzy set (T-SFS) is a generalization of the spherical fuzzy set (SFS). HF set has a significant role for modelling disagreements of the decision-makers over membership degree of an element. Also, T-SFS is quite effective in the modelling of the uncertainty for decision-making (DM) problems. In this paper, we define the concept of hesitant T-spherical fuzzy (HT-SF) set (HT-SFS) by combining concepts of HF set and T-SFS, and present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Jin et al ( 2021 ) initiated several Hamacher aggregation operations involving interval-valued T-spherical fuzziness in uncertain surroundings and employed them to explore multiple-criteria choice procedures for performance evaluation. Karaaslan and Al-Husseinawi ( 2022 ) defined the notion of hesitant T-SF sets and the corresponding Dombi aggregation operators, propounded an innovative approach to group decision analysis, and employed it to the issue of choosing the most qualified applicants for assistant professorships at universities. Khan et al ( 2022 ) exploited the notion of power aggregation operations in a complex T-SF framework to formulate useful performance measures of the software package.…”
Section: Literature Review and Research Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al ( 2021 ) initiated several Hamacher aggregation operations involving interval-valued T-spherical fuzziness in uncertain surroundings and employed them to explore multiple-criteria choice procedures for performance evaluation. Karaaslan and Al-Husseinawi ( 2022 ) defined the notion of hesitant T-SF sets and the corresponding Dombi aggregation operators, propounded an innovative approach to group decision analysis, and employed it to the issue of choosing the most qualified applicants for assistant professorships at universities. Khan et al ( 2022 ) exploited the notion of power aggregation operations in a complex T-SF framework to formulate useful performance measures of the software package.…”
Section: Literature Review and Research Vacanciesmentioning
confidence: 99%
“…Natural language expressions in T-SF settings are also beneficial for identifying the qualitative evaluation of unclear data (Akram et al 2023 ; Naz et al 2022 ; Wang 2022 ). T-SF theory can produce a successful decision-making technique for assessing and choosing options in sophisticated fuzzy environments through varied T-SF decision-analysis tools created by numerous academics (Abid et al 2022 ; Chen 2022b ; 2022d ; Karaaslan and Al-Husseinawi 2022 ; Yang and Pang 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al (2022b) exploited Aczel-Alsina t-norms and t-conorms to evolve Aczel-Alsina weighted average and geometric operation in T-SF settings for resolving decision-making issues. Karaaslan and Al-Husseinawi (2022) presented arithmetic and geometric averaging operations in hesitant T-spherical Dombi fuzzy settings for group decision-making. Khan et al (2022) employed power-weighted averaging and geometric operations in complex T-SF settings to suggest a performance measurement method under uncertainties.…”
Section: T-sf Theory In Uncertain Decision Contextsmentioning
confidence: 99%
“…In particular, based on Table 1, it can be easily observed that many researchers discussed the modularization of multiple-criteria choice methods in the context of T-SF sets with aggregation operations or averaging (i.e. mean) operations, such as Akram and Martino (2022), Al-Quran (2021), Chen et al (2021), Gurmani et al (2022), Hussain et al (2022aHussain et al ( , 2022b, Karaaslan and Al-Husseinawi (2022), Khan et al (2022), Liu et al (2021c), Mahnaz et al (2022), Wang (2021), Wang and Zhang (2022), Yang and Pang (2022), Yang et al (2021), Zedam et al (2022), andZeng et al (2021). That is, many of the above works of literature focus on models of aggregating or averaging operations, which belong to a measurement of the central tendency of a finite set of T-SF information.…”
Section: T-sf Theory In Uncertain Decision Contextsmentioning
confidence: 99%
“…Moreover, in 2021, Seikh and Mandal [27] introduced Dombi operators on IFS. Karaaslan and Husseinawi [28] presented hesitant T-spherical fuzzy Dombi aggregation operators and their applications in MADM in 2022.…”
Section: Introductionmentioning
confidence: 99%